A CRITICAL JUNCTURE? COVID-19 AND THE FATE OF THE U.S.–CHINA STRUGGLE FOR SUPREMACY. (September 2021) - Ameyaw-Brobbey, Thomas
This article compares the United States' and China's international efforts of responding to the current coronavirus (COVID-19) pandemic and considers how the global public is receiving both to project how such measures would likely shape the international leadership competition. How do the international efforts of the United States and China on COVID-19 affect their respective soft power? How does the global public perception of the United States' and China's COVID-19 efforts affect their competitive advantage for global leadership? Based on the theory of soft power, I use Europe and Africa as cases with global perception data from the Pew Research Center (2017–2020) to argue that China would likely win some admiration for its COVID-19 efforts. However, it is unlikely to substantially shape positive global public perception of China to gain a competitive edge over the United States. This argument is based on the narrative China presents in the pandemic, its diplomatic style, and the ideational attachment the U.S. style has established. I utilize a phenomenological approach with narrative analysis.